A Chinese female Morvan patient with LGI1 and CASPR2 antibodies: a case report. Issue 1 (December 2016) - Zhang, Li; Lu, Qiang; Guan, Hong-Zhi; Mei, Jun-Hua; Ren, Hai-Tao; Liu, Ming-Sheng; Peng, Bin; Cui, Li-Ying
Abstract Background Morvan syndrome is a rare disorder characterized by the combination of peripheral nerve hyperexcitability, encephalopathy and dysautonomia with marked insomnia. It was reported to have association to antibodies to voltage-gated potassium channels including contactin associated protein-like 2 antibodies (CASPR2-Ab) and leucine-rich glioma inactivated protein 1 antibodies (LGI1-Ab). LGI1-Ab was reported to associate with seizures, amnesia, confusion, hyponatraemia and a good prognosis, while CASPR2-Ab with peripheral presentations, probable risk for tumor and a poor prognosis. The vast majority of Morvan syndrome patients were male, with normal magnetic resonance imaging of the brain. Case presentation We report a female case presenting with a combination of bilateral leg pain, widespread myokymia, memory disturbance, seizure, hyperhidrosis and insomnia. She had antibodies targeting CASPR2 and LGI1, tested by the indirect immunofluorescence test, which demonstrated the diagnosis of typical Morvan syndrome as well as classical limbic encephalitis. Cranial MRI revealed bilateral hyper-intensity of the medial temporal lobe, insular lobe and basal ganglia on T2/FLAIR and DWI sequence. As the treatment carried on, her serum LGI1-Ab disappeared and her memory loss, seizure and confusion quickly relieved. But her peripheral presentations did not relieve until serum CASPR2-Ab turned negative. Intravenous immunoglobulin treatment showed limited efficacy while she achieved almost complete remission with corticosteroids therapy. Conclusions This case provides a rare female resource of Morvan syndrome, which is the first patient with both CASPR2-Ab and LGI1-Ab positive Morvan syndrome in China and one of the few female patients with Morvan syndrome reported so far. Through the detailed analysis of her clinical course, the diverse and overlapping clinical phenotype of CASPR2-Ab and LGI1-Ab in patients with Morvan syndrome was obvious and interesting.